The Reality of Academic Freedom at the University Level in the Kingdom of Saudi Arabia - Mohammad S. Alzboon; Abdel Rahman M . Al Barjes (University of Science and Technology, Yemen, 2015)
This study aimed to find out the reality of academic freedom at the university level in the Kingdom of Saudi Arabia, the study population consisted of faculty members at universities in the North in the Kingdom of Saudi Arabia, and the study sample of 296 faculty members , for the purposes of achieving the goal of the study was the development of study tool ( questionnaire ) , were distributed after the confirmation of sincerity and persistence .         After collecting the data is the process of statistical analysis using the (SPSS), by calculating the degree of appreciation of faculty members of the reality of the degree of academic freedom at the university level in Saudi universities, study results showed that the reality of academic freedom at the university level in the Kingdom of Saudi Arabia came moderately . It also showed a statistically significant difference between the estimates of faculty members to exercise the degree of academic freedom, due to the variable and in favor of the female sex and the lack of differences between the estimates of faculty members to exercise the degree of academic freedom, due to the variables of experience and academic rank variable .           The study recommended the need for the university to provide academic freedom for all faculty members represented in decision-making and administrative and financial situation , relevant rules and regulations and procedures that help to achieve the objectives of education and research.